KAMPANYE MEMASYARAKATKAN PENGGUNAAN SEPEDA KEPADA MAHASISWA UNIVERSITAS NEGERI PADANG MELALUI MEDIA POSTER - Bambang Purnomo; Muzni Ramanto; Ady Rosa (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
AbstractState University of Padang (UNP) is one of the country's leading higher education institutions in West Sumatera. In a government and private institutions, the use of means of transportation very important role to support the smooth running of activities undertaken. Currently, a widely used means of transportation at the State University of Padang is the kind of motor vehicles and motor cars. Phenomena occurring at the State University of Padang on the motor vehicle is, the onset of discomfort on the move. These include discomfort, noise pollution, air pollution, public order disturbances caused by motor vehicles. The design of this poster campaign through the media aims to make comfortable and orderly atmosphere in the campus environment, and make Padang State University academic community more healthy without air pollution. The method used in this campaign using the two methods. The first method of data collection and data analysis methods. Data collection methods, the authors do by way of interviews, observation, and documentation. Second, the method of data analysis using SWOT analysis. From the SWOT analysis will be obtained Strength, Weakness, Oppurtunity, and the Threat of this campaign. The results of the analysis of the campaign to popularize the use of bicycles to the students of UNP media is the creation of a poster design and its supporters are referring to the principles and rules of design in general.Kata Kunci: Kampanye, Sepeda, Mahasiswa, Poster